Students’ Mathematical Thinking and Comprehensive Mathematics Instruction (CMI) Model - Nita Delima; Yaya S. Kusumah; Siti Fatimah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2021)
Several facts about learning mathematics in high school, show that students' mathematical thinking skills are still low. Therefore, there needs to be an effort to increase these variables, considering that these variables are very important in supporting students' academic achievement. This study discusses the application of a comprehensive mathematics instruction (CMI) model in mathematics learning as an effort to improve students' mathematical thinking. This research is a quasi-experimental research. The sample was taken purposively from the population of high school students in Subang Regency, West Java, Indonesia. The instruments used in the research consisted of a mathematical thinking ability test and an observation sheet. Mathematical thinking ability is built by four important aspects, namely specializing, generalizing, conjecturing and convincing. The CMI model is a learning model that accommodates three stages, namely develop, solidify and practice. Each of these stages provides the opportunity for students to develop specializing, generalizing, conjecturing and convincing aspects. The results showed that the CMI model can improve students' mathematical thinking abilities. Thus, the CMI model deserves to be used as an innovation in mathematics learning.